2009
DOI: 10.1099/vir.0.013417-0
|View full text |Cite
|
Sign up to set email alerts
|

Mouse vaccination with dendritic cells loaded with prion protein peptides overcomes tolerance and delays scrapie

Abstract: Prion diseases are presumed to be caused by the accumulation in the brain of a pathological protein called prion protein (PrP) scrapie which results from the transconformation of cellular PrP, a ubiquitous glycoprotein expressed in all mammals. Since all isoforms of PrP are perceived as self by the host immune system, a major problem in designing efficient immunoprophylaxis or immunotherapy is to overcome tolerance. The present study was aimed at investigating whether bone-marrow-derived dendritic cells (DCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Many vaccination regimens in experimental mouse models of scrapie resulted in prolonged incubation periods, which were most often ascribed to anti-PrP antibodies (Pankiewicz et al, 2006;White et al, 2003;Peretz et al, 2001;Polymenidou et al, 2004;Bachy et al, 2010;Rosset et al, 2009). To our knowledge, our study constitutes the prime evidence that an immune manipulation can interfere with prion progression during the symptomatic period.…”
Section: Discussionmentioning
confidence: 99%
“…Many vaccination regimens in experimental mouse models of scrapie resulted in prolonged incubation periods, which were most often ascribed to anti-PrP antibodies (Pankiewicz et al, 2006;White et al, 2003;Peretz et al, 2001;Polymenidou et al, 2004;Bachy et al, 2010;Rosset et al, 2009). To our knowledge, our study constitutes the prime evidence that an immune manipulation can interfere with prion progression during the symptomatic period.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have indicated that antigen sensitized DCs, when used as a vaccine, can overcome (i.e., break) immune tolerance. This has been specifically reported in a mouse model of scrapie induced by prion proteins, 47 as well as in mouse models of tumor induction 48 and hepatitis B infection. 49 Also, as previously indicated both a-Syn and Ab have successfully been able to stimulate antibody responses in appropriate Tg animal models.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, research has focused on the initiation of T-cell based immunity in order to break the natural tolerance to PrP C . In one such study, dendritic cells were pre-loaded with prion protein peptides and injected into wild-type mice at 15 day intervals [111]. Spleen cells and sera collected 10 days after the final challenge demonstrated that T cells could be induced to produce a good lymphokine response as defined by Interferon-gamma and IL-4 release.…”
Section: Immune-based Approaches To Prion Disease Therapymentioning
confidence: 99%